Level of knowledge and behaviour of society district Jombang about covid-19 - Kahan Tony Hendrawan; Arnaz Anggoro Saputro (CV Rezki Media, 2021)
Occurrences of the COVID-19 outbreak have appeared in 215 countries worldwide, including the country of Indonesia. Jombang is a regency with a higher increase in COVID-19 patients than its neighboring cities and regencies in the province of East Java. The number of positive COVID-19 patients in Jombang currently stands at 64 documented cases. To reduce the increase in the number of new cases, all layers of the public and government are required to take part. The purpose of this research is as knowledge about Covid 19 is very important for the community so that people can make decisions in behaving appropriately to break the chain of transmission of Covid 19. This research is quantitative with an analytical correlation design. The sample count is 144 respondents randomly chosen to fill in a Google Form that was distributed via WhatsApp to the general public of the regency of Jombang. The data was analyzed using the Spearman Analytical Correlation method. Results show that the public of Jombang regency included into the category who possess a good knowledge of COVID-19 is (90%) with only (10%) in the category with enough knowledge. The public of Jombang in dealing with the COVID-19 pandemic, such as wearing a mask, practicing hand hygiene, and physical/ social distancing, shows a percentage of (95,8%) included in the good category with only (4,2%) in enough category.